Case report: Thromboembolic heartworm induced lower limb necrosis in a dog - Taweethavonsawat, Piyanan; Rattanapinyopituk, Kasem; Tachampa, Kittipong; Kiertkrittikhoon, Srireepong; Jitsamai, Wanarit; Klomkleaw, Wuthichai; Choisunirachon, Nan; Komin, Kiatpichet (Frontiers in Veterinary Science, 2022)
A 9-year-old spayed female boxer suffered from lameness in both hindlimbs with a perforated paw wound. Additionally, a linear, worm-like creature was penetrating out from the wound. On examination, the dog was emaciated and infested with heartworms, detected through fresh blood smear, echocardiography, and transabdominal ultrasonography. Adult heartworms were detected at the right atrium, right ventricle, and pulmonary artery including the distal abdominal aorta, external iliac, and femoral arteries. Adult heartworms were surgically removed from both the heart (n = 8) and the femoral arteries (n = 5). Unfortunately, not all heartworms could be removed from these locations due to the extent of the heartworm infection. The opened, ischemic wounds in the distal limbs progressively expanded and the dog subsequently died, possibly due to caval syndrome complications and septicemia. The autopsy showed an atrial septal defect that was not previously detected and a total of 25 adult heartworms were collected from the perforated paw, heart, pulmonary, and femoral arteries. All worms collected during the autopsy process were molecularly confirmed to be Dirofilaria immitis.